Christian gathering and the digital ecclesia: A post-COVID-19 reading of Hebrews 10:25 - Sakitey, Daniel; van Eck, Ernest (Hervormde teologiese studies, 2025)
This article is a post-coronavirus disease 2019 (COVID-19) reflection on the phrase mē egkataleipontes tēn episunagōgēn heautōn [not forsaking our own gathering] in Hebrews 10:25. The writer of Hebrews warned members of his faith community against the ethos of absenting themselves from their own meetings, citing the eschatological consequences of such a habit. The author’s choice of episunagōgē, which is the object of the neglect, may have been influenced by the unhealthy relationship between 1st-century Christianity and Judaism, especially its place of worship – the synagogue [sunagōgē]. In translating episunagōgē into Ewe, translators chose fufofewo [places of gathering] and takpefewo [places of meeting]. However, fufofewo and takpefewo are Ewe renditions of sunagōgē and not episunagōgē. These Ewe renditions reinforce the traditional Christian understanding of episunagōgē as a place of worship. Employing a combination of exegetical and mother tongue hermeneutics as its methodologies, the article chronicled how the traditional interpretation and application of Hebrews 10:25 throughout the epochs of Christianity, was challenged by the outbreak of the Covid-19 pandemic and makes recommendations for the future of Ewe-Ghanaian ecclesiology which is the focus of this article. The COVID-19 pandemic that devastated the economy of nations and human lives also disrupted Christian worship, it temporarily locked down churches, and compelled them to celebrate Easter - the most important event on the Christian calendar - virtually. This ecclesiastical experience, which deprived Ewe-Ghanaian worshippers of their freedom of fellowshipping together and put to the test their conservative ecclesiology, exposed the church to a new paradigm in its liturgical life and ministry. This article, therefore, views the digital worship space as the new normal in Ewe-Ghanaian ecclesiology and recommends that the church in Ghana must integrate digital worship into its liturgical culture and invest into digital infrastructure that would serve the liturgical needs of its members both at home and abroad.ContributionThe article contributes to the academic knowledge on the interpretation of Hebrews 10:25, re-emphasising the importance of context sensitivity in biblical hermeneutics in African Christianity.